Iodine insufficiency as a dietary issue in elderly people and its connection with pathology of thyroid - Simurova, Natalia; Postol, Svitlana; Kravchenko, Victor (My University, 2016)
Pathologies, that may develop due to microelement insufficiency, are very variable and connected to low synthesis of thyroid hormones. Eldery people start experience some health problems. And among other, problems with thyroid are playing very important role that shouldn’t be ignored. 53 patients in the age of 40-78 years were involved in the research. The easiest and the most effective way to compensate insufficient supply of iodine is regular intake of the iodized salt. Патології, які можуть розвинутися через недостатність мікроелементів, різноманітні і пов'язані з недостатнім рівнем гормонів щитовидної залози. Люди похилого віку починають відчувати все більше проблем зі здоров'ям. І серед іншого, проблеми з щитовидною залозою відіграють дуже важливу роль, яку не можна ігнорувати. У дослідженні брали участь 53 пацієнти віком 40-78 років. Найпростіший і ефективний спосіб компенсувати нестачу йоду - регулярне споживання йодованої солі.
Keywords: iodine insufficiency; elderly patients; prevention; йодна недостатність; пацієнти похилого віку; профілактика; кафедра харчової хімії